PENGARUH MODEL THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI KEMAMPUANAWAL SISWA - Trias Tuti (Mat-Edukasia, 2020)
The purpose of this research is to describe the mathematical problem-solving ability in terms of the students' initial ability to use the Cooperative Think Think Share (TPS) type model better than conventional learning of students of class VIII SMP N 12 Merangin 2019/2020 academic year. The research method used was an experiment. The research design was a 2 x 3 factorial design. The sampling technique used was probability sampling. Data collection techniques through tests. Based on the prerequisite test results of data analysis, it is known that the data is normally distributed and not homogeneous for hypotheses 1, 3 and 4, while for data with normal and homogeneous distribution for hypothesis 2. The test results show that: for hypotheses 1, 3 and 4 are mathematical problem solving abilities with models Medium, low and overall early think pair share are better than conventional learning. For hypothesis 2, the mathematical problem solving ability with high initial ability think pair share models is no better or the same as conventional learning.